Influence of disinfecting solutions on the surface topography of gutta-percha cones: a systematic review of in vitro studies - Lora Mishra; Gathani Dash; Naomi Ranjan Singh; Manoj Kumar; Saurav Panda; Franck Diemer; Monika Lukomska-Szymanska; Barbara Lapinska; Abdul Samad Khan (Restorative Dentistry & Endodontics)
The surface integrity of gutta-percha cones is a crucial factor in the success of endodontic procedures. Disinfecting solutions play a pivotal role in sterilizing gutta-percha cones, but their influence on gutta-percha surface topography remains a subject of concern. This systematic review aimed to present a qualitative synthesis of available laboratory studies assessing the influence of disinfecting solutions on the surface topography of gutta-percha and offers insights into the implications for clinical practice. The present review followed PRISMA 2020 guidelines. An advanced database search was performed in PubMed, Google Scholar, Embase, Scopus, LILAC, non-indexed citations and reference lists of eligible studies in May 2024. Laboratory studies, in English language, were considered for inclusion. The quality (risk of bias) of the included studies was assessed using parameters for in vitro studies. A total of 28 studies were included in the qualitative synthesis. Based on the included in vitro studies, surface deposits and alterations in the physical properties of gutta-percha cones were observed after the disinfection protocol. A comprehensive review of the available literature indicates that the choice of disinfecting solution, its concentration, and immersion time significantly affect the surface topography of gutta-percha cones.